ANALYSIS OF CONSTRUCTION WORK E-TENDERING IMPLEMENTATION BASED ON PRINCIPLES OF PROCUREMENT OF GOODS AND SERVICES IN JEPARA REGENCY GOVERNMENT (Science and Technology (SciTech), 2023)
Construction service jobs in the current government are inseparable from the process of selecting construction service providers, which are obtained through e-procurment. In Jepara Regency itself, the process has been carried out to select construction service providers based on the Construction Services Law No. 2 of 2017 and Presidential Regulation no. 12 of 2021 concerning changes to presidential regulation no. 16 of 2018 regarding procurement of government goods/services which in it directs the Regional Government to carry out tenders in accordance with the principles of procurement. Procurement data for 2020 and 2021 in Jepara Regency shows a budget efficiency of 8.37%. The data shows that the principle of procurement has been implemented in the e-tendering process. And from the results of research using qualitative methods, the average value of the questionnaire results is 6.07 which is in the very good category. Validity and reliability tests show valid and reliable results. The research was conducted on procurement actors and examined 6 (six) procurement stages.